Effect of soil coefficients and Poisson’s ratio on the behavior of modified Euler-Bernoulli beam lying on Winkler foundation - SINIR , B. Gültekin (International Journal of Computational and Experimental Science and Engineering, 2017)
Beside the geometric acceptations on deriving the mathematical model of the structural elements the material specifications can affect their different fundamental responses. Respectively, in this study standard Euler-Bernoulli beam theory is adjusted and modified to comprise the effect of Poisson’s ratio on the mechanical model of the beam. The interaction between beams and the soil medium below the beams alter the actual behavior of the beams. In this study, the equation of motion of the beam lying on Winkler foundation is derived via adopting the extended Hamilton principle. This new formulation is used to investigate the soil-structure interaction features of the modified beam with uniform cross sectional area. Three different soil types is considered. The non-dimensional mathematical model of the proposed beam is also obtained. Finally, the effect of the Poisson’s ratio and foundation spring coefficient on the behavior of the proposed beam is discussed and demonstrated through given diagrams.